2016
DOI: 10.1242/jcs.179291
|View full text |Cite
|
Sign up to set email alerts
|

Complement-mediated ‘bystander’ damage initiates host NLRP3 inflammasome activation

Abstract: Complement activation has long been associated with inflammation, primarily due to the elaboration of the complement anaphylotoxins C5a and C3a. In this work, we demonstrate that the phagocytosis of complement-opsonized particles promotes host inflammatory responses by a new mechanism that depends on the terminal complement components (C5b-C9). We demonstrate that during the phagocytosis of complement-opsonized particles, the membrane attack complex (MAC) of complement can be transferred from the activating pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 64 publications
0
40
0
Order By: Relevance
“…Recently, MAC has been suggested to provide both the priming and the activation signals for inflammasome activation because experiments indicated that MAC-mediated 'bystander' damage could lead to NLRP3 activation in mouse macrophages [48] . Specifically, this study showed that phagocytosis of complement-opsonized particles could promote inflammasome activation by a novel 'bystander' mechanism involving the transfer of MAC from the activating particle to a nearby cell.…”
Section: Inflammasome Priming Via Complementmentioning
confidence: 99%
“…Recently, MAC has been suggested to provide both the priming and the activation signals for inflammasome activation because experiments indicated that MAC-mediated 'bystander' damage could lead to NLRP3 activation in mouse macrophages [48] . Specifically, this study showed that phagocytosis of complement-opsonized particles could promote inflammasome activation by a novel 'bystander' mechanism involving the transfer of MAC from the activating particle to a nearby cell.…”
Section: Inflammasome Priming Via Complementmentioning
confidence: 99%
“…An interesting recent report links the recovery processes described above with inflammasome activation; MAC internalization and incorporation into Rab5+ endosomes facilitated NF‐kB signaling through non‐canonical pathways, raising the interesting possibility that MAC continues to exert its pro‐inflammatory effects even after removal from the cell surface. In this respect, the recent description of MAC‐dependent inflammasome activation in “bystander” cells is relevant . Macrophage uptake of complement opsonized particles caused NLRP3 inflammasome activation but only when particles were opsonized in the presence of an intact terminal pathway; during this process, MAC was “transferred” to the macrophage membrane by poorly defined routes to cause sublytic damage.…”
Section: Impact Of Structures On Understanding Of Nucleated Cell Respmentioning
confidence: 99%
“…Thus, it will be thrilling to investigate the role of complement in other forms of cell death such as necroptosis (programmed necrosis), pyroptosis (inflammasome‐induced), or autophagic cell death. In this context, it is remarkable that sublytic membrane attack complex (MAC) is able to induce the NLRP3 inflammasome in vivo and that MAC can be transferred from complement‐opsonized particles after phagocytic uptake to the macrophage plasma membrane by a “bystander” mechanism, which finally results in inflammasome activation . The engulfment of complement‐opsonized particles results in enhanced leukocyte recruitment and promotes T helper 17 (Th17) cell biasing .…”
Section: Discussionmentioning
confidence: 99%